miR-21, miR-29c, and miR-155 as Biomarker to Develop Minimal Invasive Diagnostic in Hepatocellular Carcinoma Patient - P Lestari; N Qoriansas; D.S Tanjung; M.S. Fitria; A.I. Kartika; T. Wardana; N. Ratnasari; S.M. Harjana; T. Aryandono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Background: Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies and the third leading cause of cancer-related deaths worldwide. Incidence and mortality of HCC increase annually because of its poor prognosis. The most common cause of this condition is its characteristics with high metastasis and high recurrence after surgical treatment. So, it is become important to find new serological biomarkers for early stage detection of HCC. Plasma microRNA are being actively investigated as minimal invasive biomarkers in human cancers, including HCC.Objective: The aim of this study is to investigate the level expression of miR-21, miR-29c, and miR-155 as novel serological biomarkers for hepatocellular carcinoma.Methods: This study is quasi experimental and remain as preliminary study. Collecting for more samples is currently underway. HCC patient blood samples obtained from RSUP dr. Sardjito Yogyakarta based on specific inclusion and exclusion criteria. Blood samples were collected from 8 patients and 8 healthy controls. The collected blood samples were treated as follows: plasma isolation, RNA total isolation, cDNA synthesis, quantification by qRT-PCR, data analysis with Biorad CFX ManagerTM Softwere to determine Cq, followed by the calculation of expression levels using Livax Methods.Result: The result showed that miR-21 and miR-155 were upregulated 1.68 fold and 2.38 fold respectively compared with healthy control, while miR-29c was downregulated 3,45 fold compared with healthy control.Conclusion: Based on the result of preliminary study, it can be concluded that miR-21 act as oncomiR, while miR-29c and miR-155 act as tumor supressor miR in HCC. The three microRNAs can be detected in HCC and can be used as minimal invasive biomarkers to detect HCC.Keywords: HCC, miR-21, miR-29c, miR-155, minimal invasive, biomarker